Implementation of Service Quality and Customer Satisfaction at KAI - Moza Muhammad Althaf; Dhimas Januar Prasetyo; Wulan Meidiva (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the implementation of service quality and its effect on customer satisfaction at PT Kereta Api Indonesia (KAI) through a qualitative literature review approach. Drawing on empirical studies published between 2019 and 2025, this research analyzes how KAI has applied the five dimensions of the SERVQUAL model reliability, responsiveness, assurance, empathy, and tangibles across its service delivery systems, including ticketing, station management, and on-train experience. Key findings from the synthesized literature indicate that service quality directly influences passenger satisfaction (?=0.74) and trust (?=0.29), while passenger satisfaction further mediates trust formation (?=0.64) (Levyda, 2021). Digital service channels, particularly the Access by KAI application, have become a central driver of service quality improvement, with studies confirming positive and significant effects on ticket sales and passenger satisfaction (Azizah Sudrartono, 2025). However, gap analysis of the Access by KAI application reveals negative service gaps across all five SERVQUAL dimensions, particularly in responsiveness (gap = ?0.73) and empathy (gap = ?0.61), indicating persistent areas requiring improvement (Khoiriyah, 2025). Employee service quality remains the primary determinant of station and on-train quality, while booking process ease determines ticketing quality. This study concludes that KAI must continue integrating digital innovation with human-centered service standards to achieve sustainable improvement in customer satisfaction.